2005
DOI: 10.1590/s1677-04202005000100009
|View full text |Cite
|
Sign up to set email alerts
|

Transport and detoxification of manganese and copper in plants

Abstract: Heavy metals like Mn and Cu, though essential for normal plant growth and development, can be toxic when present in excess in the environment. For normal plant growth maintenance of metal homeostasis is important. Excess uptake of redox active elements causes oxidative destruction. Thus, uptake, transport and distribution within the plant must be strongly controlled. Regulation includes precisely targeted transport from the macro-level of the tissue to the micro-level of the cell and organelles. Membrane trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(106 citation statements)
references
References 88 publications
2
94
0
5
Order By: Relevance
“…Furthermore, according to the anatomical changes and timing of appearance of the symptoms of Mn deficiency and toxicity observed here, we believe there are various mechanisms that act together to maintain the biochemical processes and structural plant apparatuses, resulting in different degrees of tissue organization. We also suggest that Mn detoxification of cells by activation of the antioxidant defense system (enzymatic or not), binding of Mn to complexing agents in the root system (phytochelatins, metallothioneins, histidine and nicotianamine) and subsequent deposition of Mn in the apoplast, reduction in long-distance transport of the metal-ligand complex (e.g., citrate or malate), and finally, storage inside the vacuoles (Ducic and Polle, 2005;Haydon and Cobbett, 2007), may all be more effective in the tolerant genotype, IACFoscarin 31, as pointed out by Lavres Jr. et al (2008.…”
Section: Resultsmentioning
confidence: 88%
“…Furthermore, according to the anatomical changes and timing of appearance of the symptoms of Mn deficiency and toxicity observed here, we believe there are various mechanisms that act together to maintain the biochemical processes and structural plant apparatuses, resulting in different degrees of tissue organization. We also suggest that Mn detoxification of cells by activation of the antioxidant defense system (enzymatic or not), binding of Mn to complexing agents in the root system (phytochelatins, metallothioneins, histidine and nicotianamine) and subsequent deposition of Mn in the apoplast, reduction in long-distance transport of the metal-ligand complex (e.g., citrate or malate), and finally, storage inside the vacuoles (Ducic and Polle, 2005;Haydon and Cobbett, 2007), may all be more effective in the tolerant genotype, IACFoscarin 31, as pointed out by Lavres Jr. et al (2008.…”
Section: Resultsmentioning
confidence: 88%
“…Copper excess also interferes in the activity of several enzymes (Lombardi and Sebastiani, 2005) and in some aspects associated with photosynthesis, pigment synthesis, fatty acid and protein metabolism, respiration, N fixation processes and membrane integrity, among others (Ducić and Polle, 2005). Some chloroplast proteins and the enzymes glutamine synthase (GS) and ferredoxin-dependent glutamate synthase (Fd-GOGAT), involved in the assimilation of NH 4 + , are very susceptible to heavy metal toxicity, especially Fd-GOGAT to Cu excess (Demirevska-Kepova et al, 2004).…”
Section: Coppermentioning
confidence: 99%
“…Some chloroplast proteins and the enzymes glutamine synthase (GS) and ferredoxin-dependent glutamate synthase (Fd-GOGAT), involved in the assimilation of NH 4 + , are very susceptible to heavy metal toxicity, especially Fd-GOGAT to Cu excess (Demirevska-Kepova et al, 2004). Probably its most important effect is associated with the impairment of the photosynthetic electron transport system, promoting the production of radicals that initiate the reactions of the peroxidative chain, involving membrane lipids (Ducić and Polle, 2005). In addition, Cu excess can cause alterations in the source: sink relationship, diminishing the requirements for photosynthetic products and for products that regulate Calvin cycle enzymes (Maksymiec, 1997).…”
Section: Coppermentioning
confidence: 99%
“…Although not clear, it is also assumed that Mn acts as scavenger of O ÁÀ 2 and H 2 O 2 (Ducic and Polle 2005). Several studies also revealed that supplemental Mn plays an important role in the adaptive responses of plants under various environmental stresses.…”
Section: Introductionmentioning
confidence: 99%